2018
DOI: 10.1111/bjd.16449
|View full text |Cite
|
Sign up to set email alerts
|

Children with facial morphoea managing everyday life: a qualitative study

Abstract: Understanding what it is like to live with facial morphoea from the perspectives of children and parents is important for devising ways to help children with the disorder achieve a better quality of life. Healthcare providers can help families access resources to manage anxiety, deal with bullying and construct adequate explanations of facial morphoea, in addition to providing opportunities for peer support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 37 publications
5
34
0
Order By: Relevance
“…Complementarily to their work, we found that individuals with all LS subtypes were bothered by ‘feeling different’, and that this was influenced by the visibility of their skin involvement, social support (or lack thereof) and their developmental age. Furthermore, the treatment burden reported by our participants was remarkably high compared with studies reporting from the physicians’ perspective, but was consistent with other qualitative and quantitative work . Expanding on the results of Stasiulis et al ., we found that youth with limb involvement also reported serious and impactful physical functioning limitations and related muscle and joint pain and stiffness (Table ), which are important to consider clinically.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Complementarily to their work, we found that individuals with all LS subtypes were bothered by ‘feeling different’, and that this was influenced by the visibility of their skin involvement, social support (or lack thereof) and their developmental age. Furthermore, the treatment burden reported by our participants was remarkably high compared with studies reporting from the physicians’ perspective, but was consistent with other qualitative and quantitative work . Expanding on the results of Stasiulis et al ., we found that youth with limb involvement also reported serious and impactful physical functioning limitations and related muscle and joint pain and stiffness (Table ), which are important to consider clinically.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our findings replicated and expanded on some of the major themes identified in the 2018 qualitative paper of Stasiulis et al . Complementarily to their work, we found that individuals with all LS subtypes were bothered by ‘feeling different’, and that this was influenced by the visibility of their skin involvement, social support (or lack thereof) and their developmental age.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These areas of impact make the experience of having paediatric LS a unique one that has only recently been qualitatively described in the literature in Zigler et al . (submitted) and Stasiulis et al …”
Section: Health‐related Quality Of Life Patient‐reported Outcome Measmentioning
confidence: 87%
“…Three items were subsequently added based on participant feedback. The conceptual framework was also supported by independent qualitative work from a separate institution . Although only individuals with facial involvement participated (compared with a mix of subtypes in the focus groups that were used to inform this PROM development), themes were nearly identical.…”
Section: Discussionmentioning
confidence: 99%